Plan estratégico para mejorar la gestión de la recuperación de cartera de la Empresa Importadora Industrial Agrícola del Monte - Mite Piña, Stefani Belen (2024)
The research project "Strategic plan to improve the management of portfolio recovery of the Industrial Agrícola del Monte Importing Company" addresses the need to improve efficiency in the management of collections and the recovery of overdue portfolio, especially in a context marked by global economic challenges and risks specific to the agricultural sector. The investigation is based on the problems faced by the company due to the increase in accounts receivable during the pandemic, which negatively impacted its liquidity and solvency. There is a decrease in annual portfolio turnover and an increase in the collection period, indicative of profound financial challenges. Through the inductive method and non-experimental descriptive research, information was collected through interviews and documentary review. The results reveal a variety of approaches and challenges in collections management, as well as the importance of adapting strategies to changing environmental conditions. Specific trends were identified in the management of overdue accounts, including the need to improve efficiency in recovering older accounts.........